Al-Marhum: A Grave Locator Mobile Application - Zainudin, Ahmad Aminudin; Mohamad, Shamsul (Evolution in Electrical and Electronic Engineering, 2025)
The Al-Marhum app is a mobile application that allows users to easily and accurately locate the gravesites of their lost loved ones. The app provides a smooth cross-platform experience by integrating Google Maps for exact location pinning, combining Firebase backend services, and being designed with the Flutter framework. Al-Marhum addresses common issues encountered while navigating complex cemetery layouts by offering an intuitive interface for searching for grave data by name, date of death, or grave lot number. Additionally, the app includes Islamic religious content to help users spiritually during their travels. User feedback after testing emphasized the app’s usability and effectiveness in lowering tension linked with grave placement. Future updates plan to extend the app with features including user-submitted photographs, historical cemetery information, and wider language support. Overall, Al-Marhum provides a dependable, culturally sensitive solution that bridges the gap between digital record keeping and real-world grave site navigation, allowing users to respect and remember their loved ones more easily.